Financial Performance of Mining Companies in Indonesia - Pratama Rizky Kautsar Lauw; Norhidayati Norhidayati; Syanti Dewi Harahap (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the financial performance of the mining sector in Indonesia by using the variables earnings per Share (EPS), Current Ratio (CR), and Debt to Equity Ratio (DER) as factors that affect Return on Assets (ROA) as an indicator of financial performance. This research uses secondary data in the form of financial statements of mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2023. Data analysis technique used is multiple linear regression analysis with classical assumption test. The results showed that EPS and CR had a significant positive effect on ROA, while DER had a significant negative effect. These findings contribute to the management of mining companies in improving financial efficiency and profitability, as well as a guide for investors in evaluating investment potential. The study also recommends better debt management to minimize financial risk.